Evaluation the Serum Levels of ORMDL3 among Iraqi Asthmatic Patients and Controls - Abdul Redha, Zainab Mohammed; Ahmed, Prof. Dr. Intisar Hussein (American Journal of Biology and Natural Sciences, 2024)
The aim of this study was to evaluating the serum levels of ORMDL3among Iraqi asthmatic patients.Forty-five asthmatic patients (23 males and 22 females), their age 19-70 years and 35 healthy controls (18 males and 17 females) ,their age 18-71 years were selected from Wasit Province using a convenient sampling method. Serum levels of ORMDL3 was performed using by enzyme-linked immunosorbent assay technique (ELISA) using Human- ORMDL3 kit .The results of the present study demonstrate highly significant differences, the ORMDL3 levels in the asthmatic patients were lower than that of controls (219.15264±7.02402) vs. controls (597.17106±105.99455), P= 0.0001. It is noteworthy that the ORMDL3 levels in the current study were lower significantly among male and female patients with asthma compared to the control group, (219.81270± 9.48480 versus 682.41033±.183.86672), P =0.0070, 218.46259±10.62402versus 506.91771±100.64629), P= 0.0025respectively. ORMDL3 levels revealed non-significant difference when comparing male patients with female patients 219.81270±9.48480 versus218.46259± 10.62402with a non-significant difference P=0. 9248. Based on the polymorphism of Orosomucoid-like 3 ORMDL3 rs4795405 C/T,serum levels of ORMDL3 showed asthmatic patients with homozygous CC genotypes appeared non-significant difference when compared with the healthy individuals with CC genotype 244.06078+12.84876 vs. 244.06078+12.84876 ,P= 0.5022.The patients carrying the heterozygous CT genotype revealed significant decline in ORMDL3 serum levels 212.04050+9.05509 incomparison with controls carrying this genotype618.98526+132.17806,P=0.0009. the asthmatic patients with recessive TT genotype showed non-significant decrease in ORMDL3 levels 217.35117+15.64638 versus 573.41457+281.05874 in controls ,P=0.2690. These results indicate that ORMDL3 levels in the sera of asthmatic patients for all genotypes CC,CT and TT have decreased compared to their counterparts in the control group. There were no significant differences between genotypes of ORMDL3 and its level in asthmatic patients. In conclusion, there is a potential association of ORMDL3rs4795405 C/T polymorphism and lower ORMDL3 serum levels with asthma susceptibility.